The Role of Organizational Culture in Enhancing the Effectiveness of Artificial Intelligence–Based Digital Transformation: A Systematic Literature Review - Adi Suyoso, Yosart; Wijayanti, Lely; Fauzi, Ifan Setia (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The paper examines how organizational culture enhances the effectiveness of artificial intelligence (AI)–based digital transformation. Background Problems: This paper examines why organizations that invest in AI and digital technologies often fail to achieve expected performance gains due to unsupportive cultures, and asks how specific organizational culture types can enhance the effectiveness of AI-based digital transformation. Research Methods: This study uses a Systematic Literature Review (SLR) based on the PRISMA framework to examine how organizational culture influences the effectiveness of AI-based digital transformation. From an initial 612 Scopus-indexed articles identified using relevant keywords, 11 studies that met predefined inclusion and exclusion criteria were selected for final analysis and thematic synthesis. Finding/Results: The review finds that supportive, innovation-oriented organizational cultures enable AI-based digital transformation to improve performance, while rigid and fear-based cultures hinder AI adoption and limit its benefits. Conclusion: This systematic literature review concludes that organizational culture plays a pivotal role in enhancing the effectiveness of artificial intelligence (AI)–based digital transformation by shaping digital transforming capabilities, AI adoption, and the translation of technological investments into innovation, productivity, and performance outcomes